Kelas VIII SMP Negeri 2 Tondano - Oriental Queendika Bitjoli; Derel Filandy Kaunang; Murni Sulistyaningsih (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
The low mathematical learning outcomes of students at SMPN 2 Tondano are caused by the fact that, in the mathematical learning process, especially with algebraic material, many students still have difficulty understanding and solving problems related to simplifying algebraic forms. This study uses a Quasi Experiments, which aims to determine the difference in the average learn outcome of students who use the quantum teaching learn model with the help of Wordwall media and those who only use the direct learning model at SMP N 2 Tondano in the 2025/2026 academic year. The subjects in this study were 25 student consist of 2 classes, namely class VIII-A with 14 students and class VIII-D with 11 students. The results show the average learning outcomes of students in the experiment class were 91.42, while the average learn outcome of students in the control class was 81.36. So it can be conclude the learn outcome of students who learn mathematical algebraic material using the quantum teaching model are high the average learning outcome of students who learn using the direct learning model. Keywords: quantum teaching, mathematics learning outcome